PERFORMANCE APPRAISAL AND SUPERVISION OF STATE-OWNED ENTERPRISES IN BOSNIA AND HERZEGOVINA - Nikolić, Nikola; Marin, Slobodan; Šušić, Milan (Journal of process management and new technologies, 2020)
Based on the new database of financial statements of State-Owned Enterprises (SOE) in Bosnia and Herzegovina, we can conclude that they are mostly in poor financial condition. The paper assesses the overall size and composition of the sector of state-owned enterprises, and identifies individual enterprises that affect fiscal and macroeconomic performance. Financial analysis indicates that state-owned enterprises do not contribute enough to the growth and stability of the economy. The framework for the management of state-owned enterprises has also been analyzed and we come to the conclusion that governments do not perform their ownership function in accordance with WB / OECD guidelines. Governance framework reforms are needed to foster transparency and improve accountability. Better reform of the state-owned enterprise sector could lead to an increase in total GDP by 3 percent annually.